Faktor-Faktor yang Mempengaruhi Pemberian ASI Eksklusif oleh Ibu Bekerja pada Masa Pandemi di Puskesmas Trowulan Tahun 2023 - Gana Rendra Winarti (STIKES Columbia Asia Medan, 2024)
The Covid-19 pandemic makes it difficult for breastfeeding mothers, particularly working mothers, to provide breast milk for their children. Objective: This study aims to determine the factors that influence exclusive lactation among working mothers during the Covid-19 pandemic. Method: This research employed a cross-sectional analytic design. This study's sample consisted of 60 working mothers with infants aged 6 to 12 months who met the inclusion criteria and were selected using a method of purposive sampling. Using a questionnaire, information was gathered between January and April of 2023. The data were then subjected to univariate, bivariate (chi-square), and multivariate (logistic regression) analyses. Result: During the Covid-19 pandemic, the variables education level (p 0.031), knowledge level (0.004), work duration (p 0.010), breastfeeding facilities at work (p 0.001), family support (p 0.040), and health worker support (p 0.012) were significantly related to exclusive breastfeeding among working mothers in Puskesmas (Primary Health Center) Trowulan work area. Age, social culture, and husband's support do not correlate with exclusive breastfeeding (p>0.05). Conclusion: After controlling for other variables, the most influential factors in providing exclusive lactation to working mothers during the Covid-19 pandemic are support from health workers, breastfeeding facilities, and work duration.